INNOVATIVE REFORM OF PUBLIC ADMINISTRATION: METHODOLOGICAL SUPPORT FOR THE ADOPTION AND IMPLEMENTATION OF THE STRATEGIC DECISIONS - Popov S.A. (Pressing Problems of Public Administration, 2015)
The known managerial situation in terms of structuring problems implementing modern problems of the effectiveness of the innovative renewal of the public authorities body. In order to ensure effective management of innovations in the system selected a rational model of decision and implementation of the strategic decisions. Fleshed out its stages (training, development, adoption and implementation) and their components, as well as for each of them characterized by an appropriate methodological support.